T-lymphocyte navigation and migration: beyond the PI3K paradigm. (20th March 2007) - Smith, L.; Webb, A.; Ward, S.G.
Abstract : The co-ordinated and directional trafficking of T-lymphocytes in lymphoid and peripheral tissues is an important process in lymphoid development, immunosurveillance and immune responses. Members of the chemokine superfamily play a key role in providing navigational cues for T-cells and chemokine receptors couple with a wide range of biochemical signals including phosphoinositide lipid metabolism, elevation of intracellular calcium levels, activation of a wide array of protein kinases as well as small GTPases. One of the most robust biochemical signals elicited by chemokines in T-lymphocytes is the activation of several members of the PI3K (phosphoinositide 3-kinase) family. In many cell systems, PI3Ks are known to contribute to several aspects of the migratory machinery, although their role in T-cell migration has been unclear and will be considered in the present paper.